Development of Airfield Lighting System Digital Learning Media: An Application Usability Testing - Amalia, Direstu; Soleh, Asep Muhamad; Febriansyah, Adha; Rizko, Rio; Salbiah, Siti; Suryan, Viktor; Septiani, Virma (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to evaluate the usefulness of a game-based learning tool called the airfield lighting system that uses both VR and AR technology in the classroom. The quantitative research method uses a survey to gather data and test the application in two classes. The application’s usability is represented by data analysis that uses the User Experience Questionnaire (UEQ) model to quantify two aspects: hedonic and pragmatic quality. The study’s findings display the means of the positive value scales, indicating that the pragmatic quality score was 2.538 and the hedonic quality score was 2.548. In addition, To gain a more comprehensive understanding of a product’s quality, we also assess the product’s measured user experience by contrasting it with the outcomes of other well-known products. The results are interpreted within the 10 percent best results range, indicating “excellent” for five instruments and “above average” for novelty instruments. The result presents six instruments of usability level: efficiency, perspicuity, dependability, stimulation, and novelty. This usability test suggests using the airfield lighting system application as the learning medium for student-centered learning.